2004
DOI: 10.1021/bc049891g
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Modified Polyethylenimine Polymers for Gene Delivery

Abstract: Linear and branched poly(ethylenimines), lPEI and bPEI, respectively, grafted with beta-cyclodextrin are prepared to give CD-lPEI and CD-bPEI, respectively, and are investigated as in vitro and in vivo nonviral gene delivery agents. The in vitro toxicity and transfection efficiency are sensitive to the level of cyclodextrin grafting. The cyclodextrin-containing polycations, when combined with adamantane-poly(ethylene glycol) (AD-PEG) conjugates, form particles that are stable at physiological salt concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
230
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(240 citation statements)
references
References 30 publications
8
230
0
2
Order By: Relevance
“…Such a compound had been used in pDNA delivery with good results. 19,23 Tang et al used PEI-cyclodextrin as a novel multifunctional prodrug for codelivery of a conjugated chemotherapeutic agent, tegafur, and enhanced green fluorescent protein reporter plasmid DNA. 24 Similarly, Pack et al found that cyclodextrin-PEI was less toxic to HEK293 cells than PEI.…”
Section: Introductionmentioning
confidence: 99%
“…Such a compound had been used in pDNA delivery with good results. 19,23 Tang et al used PEI-cyclodextrin as a novel multifunctional prodrug for codelivery of a conjugated chemotherapeutic agent, tegafur, and enhanced green fluorescent protein reporter plasmid DNA. 24 Similarly, Pack et al found that cyclodextrin-PEI was less toxic to HEK293 cells than PEI.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several methods to deliver siRNA in vivo. These can be divided into physical and mechanical methods (hydrodynamic tail vein injections in mice 4,5,6 , electroporation 7,8,9 , ultrasound 10 , and the gene gun 11 ); local administration 3 (intravenous injection 12 , intraperitoneal injection, subcutaneous injection); and chemical methods (cationic lipids 13,14 , polymers 15,16,17,18,19,20 , and peptides 21,22,23,24 ). However, the delivery efficiency (desired dose), uncontrollable biodistribution and delivery-related toxicitities must be carefully analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Sugar is a practically non-toxic polymer, in which the primary and secondary amines can be protonated in a physiological milieu. Sugar-based materials have been popularly used in gene delivery, while the transfection efficiencies are comparable to that of PEI [19].…”
Section: Resultsmentioning
confidence: 99%